Review of Pulmonary Sarcoidosis Progress into a Refractory Disease: Risk Factors, Biomarkers and Imaging as the Evaluation - Amalia Margaretha Lucas; Antonio Ayrton Widiastara; João Carlos Lopes; Fabiola Idinha Gama da Costa Lobo (Jurnal Respirasi, 2026)
Sarcoidosis is a multisystem, immune-mediated disorder of undetermined etiology, characterized by the formation of non-caseating granulomas. Pulmonary sarcoidosis exhibits highly variable clinical progression. Refractory pulmonary sarcoidosis (RPS), defined as disease unresponsive to standard first- and second-line therapies, remains poorly characterized. Evidence regarding the epidemiology, biomarkers, and prognostic indicators of RPS remains sparse, thereby underscoring a critical knowledge deficit. While the majority of existing studies focus on general pulmonary sarcoidosis, their findings can nonetheless yield valuable insights into refractory disease, in which chronic inflammation and therapeutic resistance pose formidable clinical challenges. Various etiological mechanisms are studied primarily in general sarcoidosis, but persistent inflammation and fibrosis are observed in RPS. Demographic factors influence general sarcoidosis and predispose to RPS. Smaller lung volumes, poor gas exchange, decreased walking distance, and oxygen desaturation aid the diagnosis of sarcoidosis, including RPS. Third-line treatment is indicated to treat RPS, with other options like lung transplantation. Refractory pulmonary sarcoidosis presents significant clinical challenges due to its complex etiology, variable progression, and treatment resistance, necessitating a deeper understanding of its risk factors, biomarkers, and therapeutic strategies. Addressing the knowledge gaps in this area is crucial for improving patient outcomes and guiding future research efforts.